Core concerns in Indian defence and the imperative for reforms (New Delhi Pentagon, 2015)
India's current defence imperatives transcend the ideological 'defence vs. butter' debate. Even while there may be no profound existential concerns, the geo-political reality of a deeply troubled neighbourhood, long legacy of border disputes with neighbours in the north and west and a widening spectrum of potential warfare from conventional and strategic to the asymmetric can be ignored at our own peril. Given the current capability gaps and infrastructure inadequacies, India requires a far more focussed pursuit of the objective of comprehensive national power with an optimal blend of fully deterrent state-of-the-art and readily deployable capabilities potentially on more than one front.
Keywords: Security Sector; Nation Security; Indian Defence; Misra, Vinod ed